Odontoameloblastoma in the posterior maxilla of a -6-years-old Ardi goat (Capra aegagrus hircus) - El-Shafaey, El-Sayed Ahmed; Hamed, Mohamed; Dewidar, Zeinab (Veterinaria Italiana, 2021)
A 6‑year‑old female Ardi goat was presented for evaluation of an expansile firm painless maxillary ovoid mass. Clinical and diagnostic imaging examination revealed a well‑ demarcated extensive mass occupying the left posterior maxilla and altering its anatomical features. Surgical excision was not deemed feasible with this apparently extensive infiltrative features of the tumor and the owner elected to euthanize the goat. Gross examination of the mass showed a grayish‑brown, multiloculated firm and gritty mass measuring 21 x 11 x 19 cm located on the left posterior maxilla. Histopathological examination revealed plexiform and follicular arranged, ameloblast ‑like odontogenic epithelium. Follicular epithelium was disintegrated leaving spaces, identical to solid multicystic ameloblastoma, intermingled with primitive myxoid stroma resembling dental papilla, teeth like hard structure as enamel and dentine, and osteodentine matrix. Based on these findings, the tumor was diagnosed as odontoameloblastoma (OA) and to our knowledge this is the first report of OA in goats.